2018
DOI: 10.6061/clinics/2018/e268
|View full text |Cite
|
Sign up to set email alerts
|

Micromass cultures are effective for differentiation of human amniotic fluid stem cells into chondrocytes

Abstract: OBJECTIVES:Articular cartilage is vulnerable to injuries and undergoes an irreversible degenerative process. The use of amniotic fluid mesenchymal stromal stem cells for the reconstruction of articular cartilage is a promising therapeutic alternative. The aim of this study was to investigate the chondrogenic potential of amniotic fluid mesenchymal stromal stem cells from human amniotic fluid from second trimester pregnant women in a micromass system (high-density cell culture) with TGF-β3 for 21 days.METHODS:M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In recent decades, in turn, the wide use of the term 'tissue spheroid' to designate the spheroid intended for research in the area of tissue engineering [39] is observed. Also noted is the term 'micromass' or 'high density micromass' , often used to describe high cell density 3D spherical cell cultures [40]. Regarding more complex spherical models, the term 'organoid' has been used, which involve various cell types and aim to mimic structures similar to mini-organs capable of executing a few more advanced roles such as hormone synthesis [3,41,42].…”
Section: Terminologymentioning
confidence: 99%
“…In recent decades, in turn, the wide use of the term 'tissue spheroid' to designate the spheroid intended for research in the area of tissue engineering [39] is observed. Also noted is the term 'micromass' or 'high density micromass' , often used to describe high cell density 3D spherical cell cultures [40]. Regarding more complex spherical models, the term 'organoid' has been used, which involve various cell types and aim to mimic structures similar to mini-organs capable of executing a few more advanced roles such as hormone synthesis [3,41,42].…”
Section: Terminologymentioning
confidence: 99%
“…These data enable con rming the in uence of the stimulation strategy used (31,54). The differentiation even without TGF-β3 stimulation can be explained by the high concentration of cells injected together into the scaffold, mimicking the condensation of chondrogenic differentiation that occurs in embryonic development (55,56). In such conditions, hAD-MSC may recapitule favorable cellular microenvironment.…”
Section: Discussionmentioning
confidence: 68%
“…After 2 h, the chondrogenic inductor medium (StemPro ® Chondrogenesis Differentiation Kit, Gibco ® , Waltham, MA, USA) was carefully added to each well and renewed every 2–3 days. After 21 days, the chondrogenic differentiation was confirmed using Alcian Blue staining [ 67 , 68 ].…”
Section: Methodsmentioning
confidence: 99%